Sobre vivências e trabalho : um olhar para o caminhoneiro, aposentado e ativo - Franceschini, Tatiane Carla Reginatto (2015)
The work plays a fundamental role in people's lifes and influences the process of living and aging. In this perspective, the dissertation tries to understand the meanings attributed to work for the retired and active trucker and identify the perceptions of this in relation to the work processes and personal experiences. It is based on a applied, exploratory and descriptive study, with a qualitative approach, through semi-structured interviews with 16 retired and active truckers of São Marcos (RS), referred as the city of the trucker. The data were analyzed through Bardin's content analysis. A first result of the research, as scientific production, was "The meaning of work for retirees and active truckers: identity, culture and social relations"; which aims at understanding the meaning that retirees and active truckers attribute to work and your implications in terms of identity, culture and social relations; and as a result shows the centrality of work, overcoming adversities in favor of the sense of freedom and achievement, and the strong brand of the cultural aspect of the worker's identity. The second production, titled "Pleasure and suffering in the trucker work" talk about the experiences of pleasure and suffering in the work of retirees and active truckers; through the following categories: working conditions, work organization, labor relations, pleasure, suffering and experiences and defensive strategies. As result is observed, on the one hand, expressions of pleasure as satisfaction, cooperation, pride, recognition, appreciation, identification with the profession and freedom; on the other hand as source of suffering is identified insecurity, fear, poor working conditions and social devaluation of the profession. Stresses that the data collected in the study subsidize the development of a third production, which will approach human aging and work